Autologous Concentrated Growth Factor Used to Treat Linear Scleroderma En Coup de Sabre: A Case Report - Wang L; Lv S; Lin W; Yang D (Dove Medical Press, 2022)
Lei Wang,1 Shuying Lv,1,2 Wenjun Lin,1,2 Dingquan Yang1 1Department of Dermatology, China-Japan Friendship Hospital, Beijing, People's Republic of China; 2School of Clinical Medicine, Beijing University of Chinese Medicine, Beijing, People's Republic of ChinaCorrespondence: Dingquan Yang, Department of Dermatology, China-Japan Friendship Hospital, Beijing, People's Republic of China, Tel +86 13901218671, Email ydqlx@163.comAbstract: Linear scleroderma en coup de sabre (LSCS) is a variant of localized scleroderma associated with band-like fibrotic lesions in the frontoparietal area. We report a case of LSCS in a woman who presented with progressive mild hyperchromia on the right side of her forehead, with dermal atrophy and hair and eyebrow loss. After the failure of conservative treatments, the patient responded dramatically to injection of autologous localized concentrated growth factor. After three treatments, the atrophy, stiffness, and angiotelectasis on the affected area had improved. No recurrence was detected 24 months after the last treatment. This is the first study describing the use of autologous concentrated growth factor injection to alleviate clinical symptoms of LSCS. This suggests that concentrated growth factor may be a treatment for LSCS in the clinic.Keywords: concentrated growth factor, linear scleroderma en coup de sabre